Tuning defects in oxides at room temperature by lithium reduction - Gang Ou (Nature Portfolio, 2018)
Defective oxides are attractive for energy conversion and storage applications, but it remains challenging to implant defects in oxides under mild conditions. Here, the authors develop a versatile lithium reduction strategy to engineer the defects of oxides at room temperature leading to enhanced photocatalytic properties.